2019
DOI: 10.1111/vco.12487
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐frequent HRAS p.Q61R somatic mutation in canine acanthomatous ameloblastoma reveals pathogenic similarities with human ameloblastoma

Abstract: Ameloblastoma is a locally aggressive odontogenic tumour that occurs in humans and dogs. Most ameloblastomas (AM) in humans harbour mutually‐exclusive driving mutations in BRAF, HRAS, KRAS, NRAS or FGFR2 that activate MAPK signalling, and in SMO that activates Hedgehog signalling. The remarkable clinical and histological similarities between canine acanthomatous ameloblastoma (CAA) and AM suggest they may harbour similar driving mutations. In this study, aimed at characterizing the mutational status of SMO, BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 33 publications
(91 reference statements)
5
21
0
Order By: Relevance
“…The predicted activation of the PI3K-AKT pathway also coincides with this trend given that aberrant RAS signaling frequently underlies dysregulation of this pathway 35 , 36 . The finding that RAS signaling contributes to CAA is consistent with its mutational landscape, which includes highly recurrent HRAS p.Q61R somatic mutations 5 , 16 . Given that HRAS p.Q61R is one of several mutations that can constitutively activate RAS 36 , 37 , the results of the present and previous studies 13 , 16 suggest that this hotspot mutation acts as a driver in CAA.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The predicted activation of the PI3K-AKT pathway also coincides with this trend given that aberrant RAS signaling frequently underlies dysregulation of this pathway 35 , 36 . The finding that RAS signaling contributes to CAA is consistent with its mutational landscape, which includes highly recurrent HRAS p.Q61R somatic mutations 5 , 16 . Given that HRAS p.Q61R is one of several mutations that can constitutively activate RAS 36 , 37 , the results of the present and previous studies 13 , 16 suggest that this hotspot mutation acts as a driver in CAA.…”
Section: Discussionsupporting
confidence: 66%
“…An additional 12 samples were used to complement RNA-seq data validation assays including reverse transcriptase quantitative PCR (qPCR) and immunohistochemistry (IHC) assays. The mutational profile of 28 of the 37 samples had previously been reported using a candidate gene approach 16 . Briefly, results showed that 15 of the 16 (93.8%) analyzed CAA samples harbored HRAS p.Q61R somatic mutations, 2 of the 8 (25%) analyzed COSCC analyzed harbored BRAF p.V600E somatic mutations, and 1 of the 8 (12.5%) analyzed COSCC samples harbored an HRAS p.Q61L somatic mutation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…New evidence on oncogenesis of canine ameloblastoma supports that ameloblastoma in dogs develops similarly to its human counterpart via mutations in the MAPK pathway ( 13 ). Thus, given the similar biologic oncogenetics between canine and human ameloblastomas, this tumor most likely also carries a small metastatic potential within the canine population.…”
Section: Discussionmentioning
confidence: 99%